Il mio nome è Lucy : l'Italia del 20. secolo nei ricordi di una transessuale - Romano, Gabriella, (1960- ) (Roma : Donzelli, 2009)
Narrativa biografia.
Keywords: Omosessuali -- Persecuzioni -- Italia -- 1943